NEW METHODS OF OPTIMIZATION OF EPILEPSY PHARMACOTHERAPY: USE OF BAYESIAN PHARMACOKINETIC MODELING - Z. А. Suslina; А. K. Sariev; D. А. Аbaimov; T. YU. Noskova; R. D. Sejfulla; V. V. Shvedkov; D. I. Prokhorov; M. V. Shiryaeva; L. А. Mota (Эпилепсия и пароксизмальные состояния, 2016)
There was carried out the therapeutic drug monitoring of antiepileptic drug carbamazepine by use of a bayesian mathematical modeling method in 47 patients with a focal epilepsy. The database of patients pharmacokinetic characteristics concerning carbamazepine was created. According the results of carbamazepine monitoring anticonvulsant dosage regimen was corrected